Negative electrode lead paste of lead storage battery for starting and stopping deep-circulation automobile as well as preparation method and application of negative electrode lead paste
By using dry mixing method and paste mixing process in the lead-acid battery negative lead paste, a deep-cycle automobile start-and-deactivated lead battery negative lead paste with improved electrochemical performance and high temperature stability was prepared, which solved the problem of the loss of active substances at deep circulation and high temperature of the negative lead paste, and significantly improved the battery's cycle life and high-rate discharge performance.
Patent Information
- Application Number
- CN202510405154.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
The negative electrode lead paste is prone to loss and fall off of active substances under deep circulation and high temperature working conditions, resulting in expansion of the battery plate and decrease in conductivity, which affects the discharge efficiency and life of the battery.
Through dry mixing, lead powder, sodium ligninsulfonate, ultrafine precipitated barium sulfate, fiber, conductive carbon material and grinding promoter were uniformly mixed, and the temperature and time were controlled during the paste combination to prepare a deep cycle automobile start-and-delay lead battery negative electrode lead paste with improved electrochemical performance and high temperature stability.
It significantly improves the performance of lead-acid batteries under deep circulation and high temperature conditions, extends the battery's cycle life (up to 49%) and high-rate discharge performance (up to 11%), and improves the overall performance of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead-acid battery production, in particular to a negative electrode lead paste for a deep-cycle automobile start-stop lead-acid battery and a preparation method and application thereof. Background Art
[0002] With the rapid development of the automobile industry, energy conservation and environmental protection have become important technical development directions. As an effective means to deal with fuel consumption and emissions, automobile start-stop systems have been widely used in modern vehicles. The system can automatically shut down the engine when the vehicle stops briefly and quickly restart it when needed, thereby reducing idling fuel consumption and exhaust emissions. However, the start-stop system places extremely high demands on batteries, including frequent start-stop, high-rate discharge, durability and deep cycle life, and especially places strict performance standards on the stability, conductivity and high-temperature durability of the negative electrode lead paste material.
[0003] Traditional lead-acid batteries are widely used in start-stop systems and have the advantages of low production cost and high safety. The patent application with publication number CN101887971A discloses a lead paste formula for energy storage batteries. By weight percentage, the positive lead paste formula is composed of the following raw materials: 6.5% to 8% dilute sulfuric acid, 10% to 11% deionized water, 15% to 30% red lead, 0.1% to 0.3% colloidal graphite, 0.08% to 0.25% stannous sulfate, 0.06% to 0.10% polyester staple fiber, and the rest is lead powder. The negative lead paste formula is composed of the following raw materials: 7.5% to 8.5% dilute sulfuric acid, 9% to 10% deionized water, 0.5% to 0.8% barium sulfate, 0.15% to 0.25% acetylene carbon black, 0.30% to 0.40% humic acid, 0.06% to 0.10% polyester staple fiber, and the rest is lead powder. The lead paste prepared by the formula and the preparation method of the invention has high initial capacity and cycle life after being made into a storage battery.
[0004] The patent application with publication number CN108134054A discloses a high-performance start-stop negative plate lead paste and its application in the negative plate of lead-acid batteries. It includes the following components by weight: 8.5-10 parts of sulfuric acid; 0.13-0.35 parts of nano barium sulfate A; 0.3-0.45 parts of nano barium sulfate B; 0.10-0.20 parts of lignin; 0.05-0.15 parts of short fibers; 0.10-0.25 parts of carbon materials; 0.05-0.15 parts of barium polyaspartate; 9-13 parts of deionized water; 74-80 parts of lead powder. This invention increases the battery's charge acceptance and low-temperature performance without adding high carbon and with less organic expansion agent content, thereby increasing the battery's life.
[0005] However, the negative lead paste is prone to loss and shedding of active substances under deep cycle and high temperature working conditions, causing the battery plates to swell and conductivity to decrease, ultimately affecting the discharge efficiency and life of the battery. Under deep cycle and high temperature conditions, electrochemical polarization will occur inside the battery, which is manifested as an increase in internal resistance of the battery, which in turn aggravates the consumption of active substances and reduces the deep cycle performance and service life of the battery. This problem is particularly evident under conditions of frequent start-stop and high-rate discharge, posing an important challenge to the reliability of start-stop batteries. Summary of the invention
[0006] In view of the above technical problems, the present invention proposes a method for preparing a negative electrode lead paste for a deep-cycle automotive start-stop lead-acid battery. The lead-acid battery prepared by the present method can maintain a low electrochemical polarization phenomenon under the frequent cycle conditions of the start-stop system, thereby extending the deep cycle life of the battery, thereby better meeting the needs of modern automobiles for start-stop batteries.
[0007] To achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a negative electrode lead paste of a lead-acid battery for deep-cycle automobile start-stop, comprising the following steps: Step 1: dry-mix lead powder, sodium lignin sulfonate, ultrafine precipitated barium sulfate (2000-4000 mesh), fiber, conductive carbon material and grinding aid enhancer, and mix them evenly to obtain mixed powder; The grinding aid and synergist is obtained by an addition reaction between ethanolamine thioglycolate and 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex under alkaline conditions; The 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex is obtained by the anti-reaction coordination reaction of 2-vinylcyclopropane-1,1-dicarboxylic acid and indium nitrate; Step 2: Add water to the mixed powder obtained in step 1, stir evenly, pour in sulfuric acid solution, control the paste temperature, and perform paste mixing. After completion, the negative electrode lead paste for the deep cycle automobile start-stop lead-acid battery is obtained.
[0008] Specifically, in parts by weight, 100-120 parts of lead powder, 0.5-1.5 parts of sodium lignin sulfonate, 0.1-0.5 parts of ultrafine precipitated barium sulfate, 0.02-0.05 parts of fiber, 0.05-0.2 parts of conductive carbon material, 0.1-1 parts of grinding aid and synergist, 10-16 parts of water, and 12-15 parts of sulfuric acid solution.
[0009] Preferably, the lead powder contains 60% to 80% PbO; and the density of the sulfuric acid solution at 25° C. is 1.350-1.450 g / cm³.
[0010] Preferably, the fiber is selected from one or a combination of polyester fiber, polyamide fiber and acrylic fiber; The conductive carbon material is selected from one or a combination of carbon black, acetylene black, carbon nanotubes, graphene, and carbon fibers.
[0011] Specifically, the preparation method of the grinding aid synergist is: According to mass parts, 25-32 parts of ethanolamine thioglycolate, 0.03-0.3 parts of 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex, 300-400 parts of N,N-dimethylformamide (DMF) and 2-5 parts of triethylamine are mixed, reacted at 60-70° C. for 60-120 minutes, and after the reaction is completed, N,N-dimethylformamide is evaporated under reduced pressure to obtain the grinding aid and synergist.
[0012] The preparation method of the 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex is: By weight, 15-30 parts of 2-vinylcyclopropane-1,1-dicarboxylic acid, 20-40 parts of indium nitrate and 200-300 parts of water are mixed, reacted at 60-70° C. for 60-120 minutes, water is distilled off, and then dried in vacuum to obtain the 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex.
[0013] The reaction mechanism of grinding aid synergist is as follows: The thiol group (-SH) has high reactivity and can easily attack the carbon-carbon double bond to form a new chemical bond. In ethanolamine thioglycolate, the thiol group acts as a nucleophile and reacts with the carbon-carbon double bond in the indium 2-vinylcyclopropane-1,1-dicarboxylate complex. Due to the excess of ethanolamine thioglycolate, the thiol group and the indium 2-vinylcyclopropane-1,1-dicarboxylate complex can also undergo a ring-opening addition reaction.
[0014] The technical effects of grinding aids and synergists are as follows: 1) The addition of grinding aids reduces the surface tension of lead powder, making it easier to wet, thereby improving its dispersibility during ball milling.
[0015] 2) The polar functional groups in the grinding aid and enhancer interact with the surface of the lead powder to form a stable adsorption layer, which prevents the agglomeration of the lead powder particles and further improves the dispersion effect. The indium dicarboxylate complex has good thermal stability and electrochemical properties. Its introduction helps to improve the stability of the negative lead paste in high temperature environments and the cycle life of the battery. The indium dicarboxylate complex may also participate in the chemical reaction on the electrode surface, improve the interface properties of the electrode, and thus enhance the charge and discharge performance of the battery. The amino functional group of ethanolamine may react with oxides or other impurities on the surface of the lead powder, remove these impurities, and expose more fresh surfaces for the ball milling process.
[0016] In summary, the grinding aid and synergist was prepared by mercapto-ene addition reaction and successfully applied to the preparation of negative electrode lead paste for deep cycle automotive start-stop lead-acid batteries. It improved the dispersion effect of ball milling, while the indium dicarboxylate complex and ethanolamine also had a positive impact on the performance of negative electrode lead paste by improving thermal stability, electrochemical performance and grinding efficiency.
[0017] Preferably, the dry mixing method is ball milling, and the ball milling process is: the ball milling speed is 200-300 rpm, the ball-to-material ratio is 5-10:1, and the ball milling time is 10-30 minutes.
[0018] Preferably, the temperature during the paste mixing process is 50-65° C., and the paste mixing time is 10-20 minutes.
[0019] The invention also provides a negative electrode lead paste for a lead-acid battery for deep cycle automobile start-stop prepared by the preparation method.
[0020] The present invention also provides a deep cycle automobile start-stop lead-acid battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode lead paste, and the negative electrode lead paste is the deep cycle automobile start-stop lead-acid battery negative electrode lead paste.
[0021] Compared with the prior art solutions, the present invention has the following beneficial effects: The negative electrode lead paste prepared by the method of the present invention enables the battery to maintain good conductivity and chemical stability under high temperature and deep cycle conditions, greatly improves the cycle life (up to 49%) and high-rate discharge performance (up to 11%) of the automotive start-stop lead-acid battery, and significantly improves the overall performance of the battery. DETAILED DESCRIPTION
[0022] In order to further understand the present invention, the present invention is further described in detail below in conjunction with preferred embodiments.
[0023] Example 1
[0024] The preparation method of the grinding aid synergist used in this embodiment is: 1. 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex: 15 g of 2-vinylcyclopropane-1,1-dicarboxylic acid (CAS: 57742-48-0), 20 g of indium nitrate, and 200 g of water were mixed, reacted at 60° C. for 60 minutes, water was distilled off, and then dried in a vacuum to obtain a 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex.
[0025] 2. Grinding aids and enhancers 25 g of ethanolamine thioglycolate (CAS: 126-97-6), 0.03 g of 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex, 300 g of DMF and 2 g of triethylamine were mixed and reacted at 60° C. for 60 minutes. After the reaction was completed, DMF was evaporated under reduced pressure to obtain a grinding aid and synergist.
[0026] A method for preparing negative electrode lead paste of a lead-acid battery for deep cycle automobile start-stop use comprises the following steps: Step 1: 100g lead powder (containing 60% PbO), 0.5g sodium lignin sulfonate, 0.1g ultrafine precipitated barium sulfate (2000 mesh), 0.02g polyester fiber, 0.05g carbon black and 0.1g grinding aid enhancer are placed in a ball mill, the ball milling speed is 200 rpm; the ball-to-material ratio is 5:1; the ball milling beads are zirconium oxide; the ball milling time is 30 minutes, and the mixture is mixed evenly; Step 2: Pour the mixed powder into a paste mixer, add 10g of deionized water, stir evenly, pour in 12g of sulfuric acid solution (density 1.350 g / cm³ at 25°C), control the temperature during the paste mixing process to be 50°C, the paste mixing time to be 10 minutes, cool down and paste out after completion, and obtain the lead paste.
[0027] Example 2
[0028] The preparation method of the grinding aid synergist used in this embodiment is: 1. 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex: 20 g of 2-vinylcyclopropane-1,1-dicarboxylic acid (CAS: 57742-48-0), 30 g of indium nitrate, and 250 g of water were mixed, reacted at 65° C. for 80 minutes, water was distilled off, and then dried in a vacuum to obtain a 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex.
[0029] 2. Grinding aids and enhancers 28 g of ethanolamine thioglycolate (CAS: 126-97-6), 0.1 g of 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex, 350 g of DMF and 3 g of triethylamine were mixed and reacted at 65° C. for 80 minutes. After the reaction was completed, DMF was evaporated under reduced pressure to obtain a grinding aid and synergist.
[0030] A method for preparing a negative electrode lead paste for a deep cycle automobile start-stop lead-acid battery comprises the following steps: Step 1: 110g lead powder (containing 70% PbO), 1g sodium lignin sulfonate, 0.25g ultrafine precipitated barium sulfate (3000 mesh), 0.03g polyamide fiber, 0.1g acetylene carbon black and 0.35g grinding aid and synergist are placed in a ball mill, the ball milling speed is 250rpm; the ball-to-material ratio is 7:1; the ball milling beads are zirconium oxide; the ball milling time is 20 minutes, and the mixture is evenly mixed; Step 2: Pour the mixed powder into a paste mixer, add 12g of deionized water, stir evenly, pour in 13g of sulfuric acid solution (density 1.4 g / cm³ at 25°C), control the temperature during the paste mixing process to be 55°C, and the paste mixing time to be 15 minutes. After completion, cool down and paste out to obtain the lead paste.
[0031] Example 3
[0032] The preparation method of the grinding aid synergist used in this embodiment is: 1. 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex: 25 g of 2-vinylcyclopropane-1,1-dicarboxylic acid (CAS: 57742-48-0), 30 g of indium nitrate, and 250 g of water were mixed, reacted at 65° C. for 100 minutes, water was distilled off, and then dried in a vacuum to obtain a 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex.
[0033] 2. Grinding aids and enhancers 30 g of ethanolamine thioglycolate (CAS: 126-97-6), 0.2 g of 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex, 350 g of DMF and 4 g of triethylamine were mixed and reacted at 65° C. for 100 minutes. After the reaction was completed, DMF was evaporated under reduced pressure to obtain a grinding aid and synergist.
[0034] A method for preparing a negative electrode lead paste for a deep cycle automobile start-stop lead-acid battery comprises the following steps: Step 1: 110g lead powder (containing 70% PbO), 1g sodium lignin sulfonate, 0.4g ultrafine precipitated barium sulfate (4000 mesh), 0.04g acrylic fiber, 0.15g carbon nanotubes and 0.75g grinding aid and synergist are placed in a ball mill, the ball milling speed is 250rpm; the ball-to-material ratio is 8:1; the ball milling beads are zirconium oxide; the ball milling time is 20 minutes, and the mixture is evenly mixed; Step 2: Pour the mixed powder into a paste mixer, add 14 g of deionized water, stir evenly, pour in 14 g of sulfuric acid solution (density 1.4 g / cm³ at 25°C), control the temperature at 60°C during the paste mixing process, and the paste mixing time is 15 minutes. After completion, cool down and paste out to obtain the lead paste.
[0035] Example 4
[0036] The preparation method of the grinding aid synergist used in this embodiment is: 1. 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex: 30 g of 2-vinylcyclopropane-1,1-dicarboxylic acid (CAS: 57742-48-0), 40 g of indium nitrate, and 300 g of water were mixed, reacted at 70° C. for 120 minutes, water was distilled off, and then dried in a vacuum to obtain a 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex.
[0037] 2. Grinding aids and enhancers 32 g of ethanolamine thioglycolate (CAS: 126-97-6), 0.3 g of 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex, 400 g of DMF and 5 g of triethylamine were mixed and reacted at 70° C. for 120 minutes. After the reaction was completed, DMF was evaporated under reduced pressure to obtain a grinding aid and synergist.
[0038] A method for preparing a negative electrode lead paste for a deep cycle automobile start-stop lead-acid battery comprises the following steps: Step 1: 120g lead powder (containing 80% PbO), 1.5g sodium lignin sulfonate, 0.5g ultrafine precipitated barium sulfate (2000 mesh), 0.05g acrylic fiber, 0.2g graphene and 1g grinding aid enhancer are placed in a ball mill, the ball milling speed is 300 rpm; the ball-to-material ratio is 10:1; the ball milling beads are zirconium oxide; the ball milling time is 10 minutes, and the mixture is mixed evenly; Step 2: Pour the mixed powder into a paste mixer, add 16g of deionized water, stir evenly, pour in 15g of sulfuric acid solution (density 1.450 g / cm³ at 25°C), control the temperature during the paste mixing process to be 65°C, and the paste mixing time to be 20 minutes. After completion, cool down and paste out to obtain the lead paste.
[0039] Comparative Example 1
[0040] A method for preparing a negative electrode lead paste for a lead-acid battery comprises the following steps: Step 1: 100g lead powder (containing 60% PbO), 0.5g sodium lignin sulfonate, 0.1g ultrafine precipitated barium sulfate (2000 mesh), 0.02g polyester fiber and 0.05g carbon black are put into a ball mill, the ball milling speed is 200 rpm; the ball-to-material ratio is 5:1; the ball milling beads are zirconium oxide; the ball milling time is 30 minutes, and the mixture is mixed evenly; Step 2: Pour the mixed powder into a paste mixer, add 10g of deionized water, stir evenly, pour in 12g of sulfuric acid solution (density 1.350 g / cm³ at 25°C), control the temperature during the paste mixing process to be 50°C, the paste mixing time to be 10 minutes, cool down and paste out after completion, and obtain the lead paste.
[0041] Comparative Example 2
[0042] The grinding aid and synergist used in this comparative example is: ethanolamine thioglycolate (CAS: 126-97-6).
[0043] A method for preparing a negative electrode lead paste for a lead-acid battery comprises the following steps: Step 1: put 100g lead powder (containing 60% PbO), 0.5g sodium lignin sulfonate, 0.1g ultrafine precipitated barium sulfate (2000 mesh), 0.02g polyester fiber, 0.05g carbon black and 0.1g ethanolamine thioglycolate into a ball mill and mix well; Step 2: Pour the mixed powder into a paste mixer, add 10g of deionized water, stir evenly, pour in 12g of sulfuric acid solution (density 1.350 g / cm³ at 25°C), control the temperature during the paste mixing process to be 50°C, the paste mixing time to be 10 minutes, cool down and paste out after completion, and obtain the lead paste.
[0044] Test Example 1
[0045] In order to verify the performance improvement effect of the negative electrode lead paste of the present invention, the negative electrode lead paste prepared in the embodiment and the comparative example was applied to the start-stop lead-acid battery, and the following key performance tests were performed: 1. Electrochemical performance test: Test battery: The prepared negative electrode lead paste was used to assemble a start-stop lead-acid battery (rated capacity 70 Ah), and the test objects were the embodiments of the present invention and the comparative example.
[0046] Test conditions: Charge and discharge tests were performed at a 2C rate, and the changes in battery discharge capacity with the number of cycles were recorded until the capacity decayed to 80% of the initial capacity.
[0047] 2. High temperature deep cycle performance test Test conditions: Simulated deep cycle charge and discharge test was carried out at 55°C, using the following charge and discharge modes: Charging: Constant current charging to 14.7V, current is 0.1C, constant voltage charging for 1 hour.
[0048] Discharge: Discharge to 10.5V at 0.2C.
[0049] Cycle: 50 times is one cycle, and the capacity retention rate after 500 cycles is tested.
[0050] 3. Discharge performance test Test conditions: At room temperature 25°C, the discharge capacity of the battery was tested at 0.1C and 2C discharge rates, and the high-rate discharge performance retention rate was calculated.
[0051] Formula: High rate discharge performance retention rate = (C high rate / C low rate) × 100%.
[0052] The test results are shown in Table 1.
[0053] Table 1 Test results
[0054] The above test results show that the negative lead paste prepared by the method of the present invention significantly improves the performance of lead-acid batteries under deep cycle and high temperature conditions. In particular, in the start-stop condition, the cycle life and high-rate discharge performance of the battery are significantly better than the negative lead paste prepared in the comparative example, and the cycle life and high-rate discharge performance of the battery are increased by up to 49% and 11%, respectively. This fully demonstrates the superiority and practical value of the present invention in the application of start-stop lead-acid batteries.
Claims
1. A method for preparing negative electrode lead paste for lead-acid batteries for deep cycle automobile start-stop, characterized in that: The following steps are involved: Step 1: dry-mix lead powder, sodium lignin sulfonate, ultrafine precipitated barium sulfate, fiber, conductive carbon material and grinding aid enhancer to obtain mixed powder; The grinding aid and synergist is obtained by an addition reaction between ethanolamine thioglycolate and 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex under alkaline conditions; The 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex is obtained by the anti-reaction coordination reaction of 2-vinylcyclopropane-1,1-dicarboxylic acid and indium nitrate; Step 2: Add water to the mixed powder obtained in step 1, stir evenly, pour in sulfuric acid solution, control the paste temperature, and perform paste mixing. After completion, the negative electrode lead paste for the deep cycle automobile start-stop lead-acid battery is obtained.
2. The method for preparing the negative electrode lead paste of the lead-acid battery for deep cycle automobile start-stop according to claim 1, characterized in that: In parts by weight, the following ingredients include 100-120 parts of lead powder, 0.5-1.5 parts of sodium lignin sulfonate, 0.1-0.5 parts of ultrafine precipitated barium sulfate, 0.02-0.05 parts of fiber, 0.05-0.2 parts of conductive carbon material, 0.1-1 parts of grinding aid and synergist, 10-16 parts of water, and 12-15 parts of sulfuric acid solution.
3. The method for preparing the negative electrode lead paste of the lead-acid battery for deep cycle automobile start-stop according to claim 2, characterized in that: The lead powder contains 60% to 80% PbO; the density of the sulfuric acid solution at 25° C. is 1.350 to 1.450 g / cm³.
4. The method for preparing the negative electrode lead paste of the lead-acid battery for deep cycle automobile start-stop according to claim 1, characterized in that: The fiber is selected from one or a combination of polyester fiber, polyamide fiber and acrylic fiber; The conductive carbon material is selected from one or a combination of carbon black, acetylene black, carbon nanotubes, graphene, and carbon fibers.
5. The method for preparing the negative electrode lead paste of the lead-acid battery for deep cycle automobile start-stop according to claim 1, characterized in that: The preparation method of the grinding aid synergist is: According to parts by mass, 25-32 parts of ethanolamine thioglycolate, 0.03-0.3 parts of 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex, 300-400 parts of N,N-dimethylformamide and 2-5 parts of triethylamine are mixed, reacted at 60-70° C. for 60-120 minutes, and after the reaction is completed, N,N-dimethylformamide is evaporated under reduced pressure to obtain the grinding aid and synergist.
6. The method for preparing the negative electrode lead paste of the lead-acid battery for deep cycle automobile start-stop according to claim 1, characterized in that: The preparation method of the 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex is: By weight, 15-30 parts of 2-vinylcyclopropane-1,1-dicarboxylic acid, 20-40 parts of indium nitrate and 200-300 parts of water are mixed, reacted at 60-70° C. for 60-120 minutes, water is distilled off, and then dried in vacuum to obtain the 2-vinylcyclopropane-1,1-dicarboxylic acid indium complex.
7. The method for preparing the negative electrode lead paste of the lead-acid battery for deep cycle automobile start-stop according to claim 1, characterized in that: The dry mixing method is ball milling, and the ball milling process is: the ball milling speed is 200-300 rpm, the ball-to-material ratio is 5-10:1, and the ball milling time is 10-30 minutes.
8. The method for preparing the negative electrode lead paste of the lead-acid battery for deep cycle automobile start-stop according to claim 1, characterized in that: The temperature during the paste mixing process is 50-65° C., and the paste mixing time is 10-20 minutes.
9. A negative electrode lead paste for a lead-acid battery for deep cycle automobile start-stop prepared by the preparation method according to any one of claims 1 to 8.
10. A deep cycle lead-acid battery for automobile start-stop, comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The negative electrode comprises a negative electrode lead paste, and the negative electrode lead paste is the negative electrode lead paste of the deep cycle automobile start-stop lead-acid battery according to claim 9.
Citation Information
Patent Citations
Lead paste formula of energy storing accumulator and preparation method thereof
CN101887971A
High-performance lead paste of starting and stopping type negative electrode plate and application thereof in negative electrode plate of lead acid battery
CN108134054A
High-temperature lead-acid accumulator cathode diachylon and preparation method
CN101330140A
Surface treatment method for AGM start-stop negative grid
CN108183239A
Lead carbon battery negative electrode material and preparation method thereof
CN108550819A